Incremental benefit of high dose compared to standard dose influenza vaccine in reducing hospitalizations - Shlomit Yaron; Matan Yechezkel; Dan Yamin; Talish Razi; Ilya Borochov; Erez Shmueli; Ronen Arbel; Doron Netzer (npj Vaccines)
Abstract Evidence regarding the high-dose (HD) vaccine’s relative vaccine effectiveness (rVE) and absolute benefit in reducing influenza-related hospitalizations compared to the standard-dose (SD) vaccine is warranted. We estimated the adjusted rVE and the number needed to vaccinate (NNV) of the HD vaccine compared to the SD vaccine among Clalit Health Services members aged ≥65 years. Among 418,603 and 393,125 members vaccinated in the 2022–2023 and 2023–2024 influenza seasons, the adjusted rVE was 27% (95% CI: −12% to 61%) for 2022–2023 and 7% (95% CI: −36% to 42%) for 2023–2024, with NNV to prevent one hospitalization event being 2262 (95% CI: 1004 to ∞) and 7662 (95% CI: 1293 to ∞), respectively. Even among the highest-risk subgroup, the NNV was 1289 (95% CI: 571 to ∞) for 2022–2023 and 4719 (95% CI: 797 to ∞) for 2023–2024. The HD vaccine exhibited a limited incremental benefit, even for individuals at the highest risk.